Stres Kerja pada Perawat Instalasi Gawat Darurat di RSUD Pasar ReboTahun 2014 - Yana, Dewi (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2015)
This study discusses work stress and the factors that affect work stress among nurses in Emergency Room in RSUD Pasar Rebo 2014. National Institute for Occupational Safety and Health (NIOSH) categorizes the factors that influence work stress, which are as job stressor, non-work, individual, and support factors. This study is conducted among 24 emergency room nurses at RSUD Pasar Rebo. Descriptive observational cross-sectional method is used in this study. The results found that 45.8% of nurses experienced high stress. The largest proportions are found in individual factor (self-esteem) and support (supervisor support).This study recommend improvements on clearer job descriptions and accurate communication and training related to management efforts in managing work stress.